PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DI CV.BARUTAMA SAMARINDA - Utomo, Didik Prasetyo (MOTIVASI, 2014)
The study aims to determine whether there is influence of job satisfaction on organizational commitment in the CV. Barutama Samarinda so there are 2 investigated the effect of which will be in penelitianini namely 1) job satisfaction 2) organizational commitment. This study was done on employees CV. Samarinda Barutama the number of 85 persons subject to the specifications of male employees and women, average age 25-45 years with a wide educational background.Analysis is done using SPPS (packade statistics for social scince) 13 for windows. The results of the analysis of test results product moment correlation with R = 0.569 and p = 0.000, then the results of the hypothesis stated that there was the influence of job satisfaction on organizational commitment of significant